Manajemen Teaching Factory Manajemen Teaching Factory untuk Penguatan Budaya K3 Berstandar Industri di SMK Negeri 1 Temanggung - Tony Tony Endro; Rejokirono Rejokirono; Rahmat Mulyono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to: (1) analyze the planning of Teaching Factory management in developing an industry-standard Occupational Health and Safety (OHS) culture; (2) describe the implementation and habituation of OHS culture in Teaching Factory practices; and (3) examine the evaluation, supervision, and follow-up processes to ensure the sustainability of OHS culture at SMK Negeri 1 Temanggung. A qualitative approach was employed, with data collected through interviews, observations, and document analysis. The participants included the principal, vice principal, heads of expertise programs, productive teachers, and students. Data validity was ensured through source and technique triangulation, while analysis used an interactive model involving data condensation, data display, and conclusion drawing. The results show that Teaching Factory planning is integrated with school policies, curriculum, and industry-standard OHS SOPs. Implementation is conducted through production-based practical learning emphasizing PPE use, compliance with safe work procedures, and disciplined work habits. Continuous evaluation, supervision, and follow-up foster safety awareness and safe work behaviour as an industry-oriented culture. This study contributes theoretically to OHS-based Teaching Factory management and practically as a model for industry-standard Teaching Factory management in vocational schools.